Electrochemically Grown Ultrathin Platinum Nanosheet Electrodes with Ultralow Loadings for Energy-Saving and Industrial-Level Hydrogen Evolution - Ding, Lei; Xie, Zhiqiang; Yu, Shule; Wang, Weitian; Terekhov, Alexander Y.; Canfield, Brian K.; Capuano, Christopher B.; Keane, Alex; Ayers, Kathy; Cullen, David A.; Zhang, Feng‑Yuan (Nano-Micro Letters, 2023)
Nanostructured catalyst-integrated electrodes with remarkably reduced catalyst loadings, high catalyst utilization and facile fabrication are urgently needed to enable cost-effective, green hydrogen production via proton exchange membrane electrolyzer cells (PEMECs). Herein, benefitting from a thin seeding layer, bottom-up grown ultrathin Pt nanosheets (Pt-NSs) were first deposited on thin Ti substrates for PEMECs via a fast, template- and surfactant-free electrochemical growth process at room temperature, showing highly uniform Pt surface coverage with ultralow loadings and vertically well-aligned nanosheet morphologies. Combined with an anode-only Nafion 117 catalyst-coated membrane (CCM), the Pt-NS electrode with an ultralow loading of 0.015 mgPt cm−2 demonstrates superior cell performance to the commercial CCM (3.0 mgPt cm−2), achieving 99.5% catalyst savings and more than 237-fold higher catalyst utilization. The remarkable performance with high catalyst utilization is mainly due to the vertically well-aligned ultrathin nanosheets with good surface coverage exposing abundant active sites for the electrochemical reaction. Overall, this study not only paves a new way for optimizing the catalyst uniformity and surface coverage with ultralow loadings but also provides new insights into nanostructured electrode design and facile fabrication for highly efficient and low-cost PEMECs and other energy storage/conversion devices. Highlights: 1 4-nm-thick Pt nanosheets (Pt-NSs) are electrochemically grown on Ti substrates for hydrogen evolution reactions. 2 Highly uniform Pt-NS surface coverage with an ultralow loading of 0.015 mgPt cm−2 is achieved. 3 99.5% catalyst savings and about 237-fold higher catalyst utilization are demonstrated.